Relationship between renal CD68+ infiltrates and the Oxford Classification of IgA nephropathy. Issue 4 (15th January 2019) - Soares, Maria F; Genitsch, Vera; Chakera, Aron; Smith, Andrew; MacEwen, Clare; Bellur, Shubha S; Alham, Nasullah K; Roberts, Ian S D
Abstract : Aims: The Oxford Classification E score (endocapillary hypercellularity) predicts renal functional decline in IgA nephropathy (IgAN) patients free from steroid/immunosuppressive (IS) therapy, but is poorly reproducible. We hypothesise that endocapillary hypercellularity reflects glomerular inflammation and that the presence of CD68‐positive cells is a more robust marker of E score. Methods and results: CD68‐positive cells were quantified in glomeruli and tubulointerstitium in biopsies from 118 IgAN patients, and cell counts were correlated with the criteria of the Oxford Classification, assigned on PAS‐stained serial sections. There was a strong correlation between median glomerular CD68 count and the percentage of glomeruli showing endocapillary hypercellularity ( r  = 0.67; P  < 0.001; r 2  = 0.45), while there was no correlation between CD68‐positive cells and mesangial hypercellularity, % segmental sclerosis, % of crescents and % tubular atrophy/interstitial fibrosis (TA/IF). ROC curve analysis demonstrated that a maximum glomerular CD68 count of 6 is the best cut‐off for distinguishing E0 from E1 (sensitivity 94.1%, specificity 71%, area under the curve = 89%). Identification of biopsies with a maximum glomerular CD68‐count >6 was reproducible (kappa score 0.8), and there was a strong correlation between glomerular CD68 counts obtained by conventional light microscopy and by image analysis ( r  = 0.80, r 2  = 0.64, P  < 0.0001). Digital image analysis revealed that tubulointerstitial CD68‐positive cells correlated moderately with % TA/IF ( r  = 0.59, r 2  = 0.35, P  < 0.001) and GFR at the time of biopsy ( r  = 0.54, r 2  = 0.29, P  < 0.0001), but not with mesangial and endocapillary hypercellularity. Conclusions: While glomerular CD68‐positive cells emerge as markers of endocapillary hypercellularity, their tubulointerstitial counterparts are associated with chronic damage.